Kenntnis und Gebrauch von Sprichwörtern bei zwei Gruppen österreichischer Jugendlicher - Lipavic-Oštir, Alja; Štavbar, Simona (Linguistik Online, 2014)
The paper presents the results and findings of the study on the levels of knowledge and use of proverbs among students from two secondary education institutions in Austria (a comprehensive school in a small town in Styria and a general upper secondary school in Vienna) based on a relevant survey. The students taking part in the study very surveyed on their knowledge of various proverbs (the proverb database in the questionnaire included 76 entries) and on the meaning of the respective proverbs. Furthermore, the students were encouraged to estimate the frequency of their use of proverbs in speaking and writing. The results show that the "rural environment" factor is not statistically significant with reference to proverb preservation (both as part of the passive as well as the active vocabulary). The male and female students enrolled in the comprehensive school from a small town in Styria know less proverbs compared to their peers, enrolled in the general upper secondary school in Vienna included in the study. What is more, the students enrolled in the comprehensive school from a small town in Styria also know the meaning and use proverbs in speaking and/or writing less frequently than their peers from the general upper secondary school in Vienna included in the study. Rather than the aspect of "rural environment", the results hint at the aspect of "type of school" to be the determining factor (comprehensive school vs. general upper secondary school). Further analyses, including additional test subjects, would provide more insight on whether the relations between proverbs and the linguistic as well as intellectual education are prominent to such an extent that a distinct degree of reception and production of proverbs could be linked to a particular type of school. The study also features an analysis of the difference between the students with reference to gender (male vs. female), with the results showing a relatively consistent distribution.